Heritage Tourism in Japan and Nepal : A Study of Shikoku and Lumbini - Ghimire, Him Lal (The Gaze: Journal of Tourism and Hospitality, 2019)
Tourism, the world’s largest industry, is essential to a community’s economic vitality, sustainability and profitability. The word ‘heritage’ in its broader meaning is frequently associated with the word ‘inheritance’, that is, something transferred from one generation to another. Heritage might look old-after all, the language of heritage focuses on preservation, revitalization, and restoration-but closer inspection usually reveals contemporary concerns. Heritage is the symbolic embodiment of the past, reconstructed and reinterpreted in the collective memories and traditions of contemporary societies rather than being perceived as a mere apotheosis of bygone times. It is concerned with exploring both tangible and intangible remnants of the past. Important criterion for a designation as a World Cultural Heritage site is the ‘‘authenticity’’ and ‘‘sincerity’’ of a candidate site. The heritage sites are the most susceptible and vulnerable sectors. A large number of significant heritage sites around the world are fragile properties, and they are faced with different challenges. Both Japan and Nepal is home to a variety of frequently occurring disasters, which can cause wide-ranging damage to its cultural resources. Japan and Nepal’s remarkable heritage is not only part of what makes both the countries a popular travel destination, but also something that needs to be properly protected, maintained and preserved, so that future generations can enjoy it as much as we do today. It has been interesting lesson to rest of the world that how Japan has been mitigating and surviving with large scale disasters. The Japanese culture, tradition and technology must have been playing significant role for this. The learning from Japan could be instrumental to manage, rebuild and develop heritage sites and tourism in Nepal. This article is the partial outcome of my Postdoctoral research in Japan.